2016
DOI: 10.1186/s12864-016-2843-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and functional analysis of mulberry type III polyketide synthases

Abstract: BackgroundType III polyketide synthases are important for the biosynthesis of flavonoids and various plant polyphenols. Mulberry plants have abundant polyphenols, but very little is known about the mulberry type III polyketide synthase genes. An analysis of these genes may provide new targets for genetic improvement to increase relevant secondary metabolites and enhance the plant tolerance to biotic and abiotic stresses.ResultsEighteen genes encoding type III polyketide synthases were identified, including six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 80 publications
5
14
0
Order By: Relevance
“…and tung ( Vernicia fordii ) [ 33 , 34 ] but is not a suitable reference gene in Arabidopsis thaliana and Rhododendron [ 35 , 36 ]. TUB s are considered to be the best reference genes in water lily and soybean [ 37 , 38 ] but are not stably expressed in Rhododendron [ 35 ]. GAPDH , EF-1α , and UBI are involved in biochemical metabolic processes in organisms and are traditional reference genes in plants [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…and tung ( Vernicia fordii ) [ 33 , 34 ] but is not a suitable reference gene in Arabidopsis thaliana and Rhododendron [ 35 , 36 ]. TUB s are considered to be the best reference genes in water lily and soybean [ 37 , 38 ] but are not stably expressed in Rhododendron [ 35 ]. GAPDH , EF-1α , and UBI are involved in biochemical metabolic processes in organisms and are traditional reference genes in plants [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCRs were completed using a StepOnePlus Real-Time PCR System (Applied Biosystems, Foster City, CA, USA). The program conditions and reaction mixture were set as described by Li et al [51]. The mulberry ACTIN3 gene was used as an internal control.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…The expressional analyses of the STS gene family members in grapevine and mulberry revealed that some STS genes exhibit differences in transcriptional responses during development and in response to environmental stresses (Vannozzi et al 2012;Shi et al 2014;Dai et al 2012). There were also differences in tissue-specific expression of some grapevine and mulberry STS gene family members (Vannozzi et al 2012;Shi et al 2014;Li et al 2016). Therefore, it is possible that distinct STS genes can be activated under various developmental or environmental cues or in different plant tissues leading to accumulation of stilbenes.…”
Section: Stilbene Biosynthesismentioning
confidence: 99%
“…The available literature data demonstrate that STS genes in sorghum, spruce, pine, peanut, and mulberry form small gene families composed of 1-10 members (Preisig-Müller et al 1999;Yu et al 2005;Paterson et al 2009;Zhu et al 2014;Warren et al 2015;Li et al 2016), while STS gene family in grapevine consists of 48 STS genes with at least 32 potentially functional ones as revealed by the genomewide analysis of the grapevine genome (Vannozzi et al 2012;Parage et al 2012). Functional analysis of nine STS genes representing most diversity of the STS gene family in grapevine performed by Parage et al (2012) revealed that the genes encode proteins possessing STS activity.…”
Section: Stilbene Biosynthesismentioning
confidence: 99%